Thyroid Disease Among Workers Exposed To Perfluorooctanoic Acid (PFOA) - Vera; Muhammad Ilyas (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background: Perfluorooctanoic Acid (PFOA) is one of the Perfluoroalkyl acids family that can affect human health. It can act as an endocrine disruptors which interfered the hypothalamus–pituitary–thyroid (HPT) axis and targeted the biosynthesis and secretion of thyroid hormones, which can caused thyroid diseases. To determine the causal relationship between PFOA and thyroid diseases, it is necessary to look for some evidence regarding this relationship. The search for evidence is also complemented by a seven-step occupational disease assessment to establish occupational diseases.Methods: The literature searching using the electronic database “PubMed”, “Cochrane”, and “Scopus” search engine. The keyword is “PFOA” “perfluoroalkyl substances” “perfluorooctanoic acid” “perfluorooctanoate” AND “thyroid disease” “thyroid function” “thyroid parameters” combined with MeSH and Title/Abstract terms. The inclusion criteria are research on humans, English language, free full article and the exclusion is duplicate articles.Result: From the five literature obtained, there are differences in results. Four articles stated that there are association between PFOA and thyroid diseases but one articles stated PFOA concentrations measured in this study were not associated with thyroid hormones.Conclusion: Althought most articles stated there are associations between PFOA and thyroid disease but it does not mean that PFOA can caused thyroid disease so it is still not clear the causal relationship between PFOA and thyroid disease especially in occupational setting.